Kepemimpinan Digital (Digital Leadership): Management Inovasi Pelayanan Pada Pemerintahan Desa Berbasis Society 5.0 - M. Refky Ramadan (PT. Hasba Edukasi Mandiri, 2026)
Digital transformation in village governance is a crucial strategy for improving the quality of public services in the modern era. This article examines the role of digital leadership in fostering technology-based service innovation management within the Society 5.0 framework. This research employs a qualitative approach, incorporating literature review and descriptive analysis of village digitalization practices in Indonesia. The results demonstrate that digital leadership plays a key role in guiding village officials to adopt technology, build a culture of innovation, and increase community participation through digital channels. The integration of Society 5.0 into village governance is realized through the utilization of technologies such as AI, IoT, big data, and cloud computing, which support evidence-based policies, service efficiency, and local economic empowerment. However, this study also identified several challenges, including digital infrastructure gaps, low technological literacy, limited funding, and data security and privacy issues. Nevertheless, with visionary leadership, national policy support, and multi-stakeholder collaboration, villages can become pioneers in the implementation of Society 5.0 at the local level. In conclusion, digital leadership is a key factor in realizing inclusive, transparent, and community-oriented village governance. This article provides theoretical contributions to strengthening the concept of digital leadership in local government, as well as practical implications in the form of strategic recommendations to accelerate village digitalization in Indonesia.